An introduction to tensors and group theory for physicists - Nadir Jeevanjee (Springer, 2015)
This textbook offers an intuitive and rigorous approach to tensors and their role in theoretical physics and applied mathematics. It demystifies tensors and provides a unified framework for understanding them in the context of classical and quantum physics.